The The Role of Employee Engagement in Mediating Transformational Leadership and Compensation on Employee Performance - Ariefiandhi, Riza; Wulansari, Puspita (International Journal of Indonesian Business Review, 2026)
Purpose – This study aims to examine the effect of transformational leadership and compensation on employee performance through employee engagement as a mediating variable at PT Infomedia Nusantara, a business-process-outsourcing (BPO) company that experienced a three-year decline in employee performance. Methodology/approach – This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 350 employees of PT Infomedia Nusantara using purposive and accidental sampling with a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. Findings – The results indicate that transformational leadership has a positive and significant effect on employee performance, whereas compensation has no significant direct effect. Employee engagement has a positive and significant effect on performance and is the strongest predictor. Employee engagement does not mediate the relationship between transformational leadership and performance, but it fully mediates the relationship between compensation and performance. Novelty – This study contributes to the human resource management literature by revealing an engagement paradox in the BPO industry: although engagement rose, performance declined. It demonstrates that compensation improves performance only when it is translated into employee engagement, while leadership drives performance directly, offering new insight for designing human-capital strategies in service organizations.